1989
DOI: 10.1007/bf00442020
|View full text |Cite
|
Sign up to set email alerts
|

Lithium increases slow wave sleep: possible mediation by brain 5-HT2 receptors?

Abstract: The effect of lithium on slow wave sleep (SWS) was studied in ten normal male volunteers using home based cassette sleep recording and automatic sleep stage analysis. Lithium increased SWS, an effect consistent with a reduction in brain 5-HT2 receptor function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
22
1
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 9 publications
8
22
1
1
Order By: Relevance
“…This result is in line with a recent report by Yang et al [26]. A slow-wave-sleepinducing effect is similarly observed under lithium treat ment [27,28], Concerning variables of REM sleep, a decrease of REM density but not a reduction of REM time was observed. Yang et al [26] had observed a signifi cant reduction of REM with a dose of 700 mg carbamaze pine.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is in line with a recent report by Yang et al [26]. A slow-wave-sleepinducing effect is similarly observed under lithium treat ment [27,28], Concerning variables of REM sleep, a decrease of REM density but not a reduction of REM time was observed. Yang et al [26] had observed a signifi cant reduction of REM with a dose of 700 mg carbamaze pine.…”
Section: Discussionsupporting
confidence: 92%
“…though the mean difference of REM sleep reduction was rather small, i.e., 3% of REM sleep. Similar signifi cant albeit minor effects on REM sleep have been re ported for lithium [27][28][29][30].…”
Section: Discussionsupporting
confidence: 60%
“…We did not find any statistically significant effect of the drug on sleep continuity in our BPD patients, but there was a trend for less sleep onset latency in the CBZ group. An enhancement in SWS has also been reported in normal subjects and depressed patients using lithium which shares thymoregulatory properties with CBZ [87,88]. As speculated by Friston et al [88], the enhancement of SWS with lithium observed by them and with CBZ by us could parallel the antagonism of the 5-HT 2 receptor.…”
Section: Discussionsupporting
confidence: 69%
“…An enhancement in SWS has also been reported in normal subjects and depressed patients using lithium which shares thymoregulatory properties with CBZ [87,88]. As speculated by Friston et al [88], the enhancement of SWS with lithium observed by them and with CBZ by us could parallel the antagonism of the 5-HT 2 receptor. The increase in SWS could also be mediated through the effect of CBZ on adenosine receptors, as adenosine neurotransmission is known to modulate neuronal activity and sleep [89], and adenosine receptor agonists are known to increase SWS in rodents [90].…”
Section: Discussionsupporting
confidence: 69%
“…Der objektive Nachweis für eine Zunahme wurde allerdings in unterschiedlichen Patientengruppen erbracht: für Tiagabin bei äl-teren Patienten und bei Patienten mit primärer Insomnie [24,56], für Valproat bei Patienten mit nächtlicher periodischer Beinbewegungsstörung (PLMD) [10] und für Gabapentin bei Patienten mit fokaler Epilepsie (Legros) [60]. Bei Lithium -mit Wirkung über 5-HT2-Rezeptoren -konnte bei Gesunden ebenfalls ein tiefschlaffördernder Effekt nachgewiesen werden [13]. Für Carbamazepin liegen widersprüchliche Studien vor.…”
Section: Behandlung Von Schlafstörungen Bei Psychischen Erkrankungenunclassified